2021
DOI: 10.1136/bmjgast-2021-000675
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of gallstone disease treatment outcomes in early cholecystectomy versus conservative management/delayed cholecystectomy

Abstract: BackgroundThe effectiveness of early cholecystectomy for gallstone diseases treatment is uncertain compared with conservative management/delayed cholecystectomy.AimsTo synthesise treatment outcomes of early cholecystectomy versus conservative management/delayed cholecystectomy in terms of its safety and effectiveness.DesignWe systematically searched randomised control trials investigating the effectiveness of early cholecystectomy compared with conservative management/delayed cholecystectomy. We pooled the ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 56 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…A higher risk of surgical complications, wound infection and sepsis has been observed in cases with conservative treatment than early cholecystectomy. A systematic review conducted in India has also reported similar findings where early surgical method was preferred with reduction in hospital stay and pain due to gall stones 9 .…”
Section: Discussionmentioning
confidence: 73%
“…A higher risk of surgical complications, wound infection and sepsis has been observed in cases with conservative treatment than early cholecystectomy. A systematic review conducted in India has also reported similar findings where early surgical method was preferred with reduction in hospital stay and pain due to gall stones 9 .…”
Section: Discussionmentioning
confidence: 73%
“…The prevalence of gallstones can vary widely across different populations and regions. Globally, gallstone prevalence varies from 0.1% to 50.5% (5). Indeed, gallstone-related complications encompass a range of conditions that can affect the biliary system and adjacent organs.…”
Section: Introductionmentioning
confidence: 99%
“…Cholelithiasis (gallstone disease) is one of the most common diseases of the gastrointestinal tract worldwide [1][2][3], and gallbladder surgeries for gallstones are the most common procedures performed in general surgery [4]. The incidence of gallstones varies from 0.1% to 50.5% worldwide [5]. In Poland, it affects about 20% of the population [6], and about 45.000 cholecystectomies (surgical removal of the gallbladder) are performed annually [7].…”
Section: Introductionmentioning
confidence: 99%